Seeking Justice: Criticizing the Decision of the Tapak Tuan District Court Number 37/Pid.Sus/2020/PN. Ttn Regarding Domestic Violence - Lubis, Andi Hakim; Sitompul, Ariman; Pinem , Serimin; Zulyadi , Rizkan; Siagian, Fahrizal (Hukum Keluarga Islam IAIN LANGSA, 2024)
The research aimed to analyze the alignment between the judge's decision in cases of domestic violence against children and the provisions of Law Number 23 of 2004 on the Elimination of Domestic Violence and Qonun Number 9 of 2019 on the Implementation of Handling Violence Against Women and Children. The study also considered moral considerations and the overall benefits. The research methodology employs a case law study, which involves examining court decisions to get insight into the application of the law in specific circumstances. Specifically, the study focuses on the Decision of the Tapak Tuan District Court Judge Number 37/Pid.Sus/2020/PN. Case law is utilized to examine court rulings to comprehend how the law is implemented in specific instances. The library research method is employed in conjunction with a sociological juridical perspective. The data for the research is sourced from the Law and various pertinent articles addressing the research difficulties. Furthermore, to bolster the ideas of the study, the paper also incorporates the findings of several empirical studies. According to the findings, it appears that the judge primarily focuses on formal factors and gives little weight to material considerations in their decision-making process. This aligns with the viewpoint expressed by Member Judge II and the concurring opinion within the panel of judges. However, the author acknowledges and values the decision made by the panel of judges. The author recognizes the challenging nature of the judges' task, as they must not only consider the legal interests involved in the case, but also consider the community's sense of justice in order to achieve legal certainty.